2006
DOI: 10.3748/wjg.v12.i28.4602
|View full text |Cite
|
Sign up to set email alerts
|

Branch retinal vein thrombosis and visual loss probably associated with pegylated interferon therapy of chronic hepatitis C

Abstract: Ophthalmological complications with interferon therapy are usually mild and reversible, not requiring the withdrawal of the treatment. We report a case of a patient who had visual loss probably associated with interferon therapy. Chronic hepatitis C virus infection (genotype 1a) was diagnosed in a 33-year old asymptomatic man. His past medical history was unremarkable and previous routine ophthalmologic check-up was normal. Pegylated interferon alpha and ribavirin were started. Three weeks later he reported pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 6 publications
0
15
0
4
Order By: Relevance
“…Over the recent years, there have been a number of anecdotal case reports of BRVO with many systemic diseases, including Bartonella [ 17 ], Behcet's disease [ 18 , 19 ], Coats' disease [ 20 ], Crohn's disease [ 21 ], deep-sea diving [ 22 ], Eales' disease [ 23 ], focal retinal phlebitis [ 24 ], high altitude [ 25 ], human immunodefi ciency virus [ 26 , 27 ], infl iximab treatment [ 28 ], interferon therapy [ 29 ], lipemia retinalis [ 30 ], during fi ngolimod treatment of multiple sclerosis [ 31 ], ocular candidiasis [ 32 ], ocular Lyme borreliosis [ 33 ], ocular tuberculosis [ 34 ], primary intraocular lymphoma [ 35 ], pseudoexfoliation [ 36 , 37 ], quetiapine fumarate [ 38 ], sarcoidosis [ 39 -42 ], superior ophthalmic vein thrombosis [ 43 ], systemic lupus erythematosus [ 44 ], Takayasu's arteritis [ 45 ], tamoxifen [ 46 ], toxoplasmic chorioretinitis [ 47 ], Tsutsugamushi disease [ 48 ], and Waardenburg syndrome [ 49 ]. As discussed above, the association of a condition with a systemic disease does not always mean cause and effect.…”
Section: Conclusion About Associated Systemic Diseases In Retinal Veimentioning
confidence: 99%
“…Over the recent years, there have been a number of anecdotal case reports of BRVO with many systemic diseases, including Bartonella [ 17 ], Behcet's disease [ 18 , 19 ], Coats' disease [ 20 ], Crohn's disease [ 21 ], deep-sea diving [ 22 ], Eales' disease [ 23 ], focal retinal phlebitis [ 24 ], high altitude [ 25 ], human immunodefi ciency virus [ 26 , 27 ], infl iximab treatment [ 28 ], interferon therapy [ 29 ], lipemia retinalis [ 30 ], during fi ngolimod treatment of multiple sclerosis [ 31 ], ocular candidiasis [ 32 ], ocular Lyme borreliosis [ 33 ], ocular tuberculosis [ 34 ], primary intraocular lymphoma [ 35 ], pseudoexfoliation [ 36 , 37 ], quetiapine fumarate [ 38 ], sarcoidosis [ 39 -42 ], superior ophthalmic vein thrombosis [ 43 ], systemic lupus erythematosus [ 44 ], Takayasu's arteritis [ 45 ], tamoxifen [ 46 ], toxoplasmic chorioretinitis [ 47 ], Tsutsugamushi disease [ 48 ], and Waardenburg syndrome [ 49 ]. As discussed above, the association of a condition with a systemic disease does not always mean cause and effect.…”
Section: Conclusion About Associated Systemic Diseases In Retinal Veimentioning
confidence: 99%
“…Por otro lado, se han descrito casos aislados de OVR en pacientes con hepatitis C tratados con interferón 23 . Nosotros tuvimos ocasión de observar un caso de OVR en un paciente con hepatitis C tratado con dicho fármaco, en el que se detectó además un déficit de proteína S.…”
Section: Discussionunclassified
“…The most common of these are retinal vein occlusion (RVO) [21,29,30,32,[49][50][51][52][53][54][55] , and non-arteritic anterior ischemic optic neuropathy (NAION) [28,49,[56][57][58][59] . Other atypical adverse events that have been reported include ocular myasthenia [60,61] , optic neuritis [62] , Vogt-Koyanagi-Harada disease [49,[63][64][65][66][67] , ocular sarcoidosis [68,69] , ocular toxocariasis [70] , neurovascular glaucoma [71] , conjunctival hemorrhage [20,26,35] , macular edema [72][73][74] , oculomotor nerve palsy [75] , trichomegaly [23] and retinal detachment [76] .…”
Section: Atypical Adverse Eventsmentioning
confidence: 99%
“…It has been suggested that there may be common elements between the pathogenesis of these complications and interferon-associated retinopathy [49,56] . Certainly, there are many cases in the literature where AION and RVO are concomitant with interferon-associated retinopathy [51,55,79] . As the atypical complications are the key causes of vision loss during antiviral therapy and interferon-associated retinopathy is common and well-described, any relationship between them should be explored in depth.…”
Section: Atypical Adverse Eventsmentioning
confidence: 99%